ANALISIS DINAMIK DAN KONTROL AKTIEF STRUKTUR NON LINIER DENGAN METODE, NEURO FUZZY - Gunawan, Tommy
This thesis is a case study on dynamic analysis and active control structure excited by dynamic load. This research is used a four-story frame modeled as shear building and local non linear stiffness modeled by Duffing's equation. Non linear dynamic equation solution is calculated by Runge Kutta Method, Linear Equivalent Method and Single Mode Method. The advantages and disadvantages of each method is explained. In case active structural control, non linear stiffness of structure is substituted with equivalent linear stiffness calculated by Linear Equivalent Method. This is done in order to use linear optimal control theory in non linear control problem. The control force is calculated using two control methods, classical discrete optimal control method with time delay and neuro fuzzy control method. The reliability of this non linear active control structure system with neuro fuzzy control method is examined by comparing the result with discrete optimal control method. It can be seen from this study that neuro fuzzy control method give a satisfactory result and can be recommended to replaced discrete optimal control method because of its simplicity and accuracy.